Handbook of Open, Distance and Digital Education 2022
DOI: 10.1007/978-981-19-0351-9_72-1
|View full text |Cite
|
Sign up to set email alerts
|

Designing Online Learning in Higher Education

Abstract: Design is critical in online learning. This chapter reviews research and practice on designing effective online courses in higher education. Firstly, the importance of design in online learning is described including asynchronous, synchronous, and bichronous delivery methods, as well as the significance of course organization and meeting learner needs in online courses. Secondly, we provide a brief overview of online course design research in higher education. Thirdly, standards and rubrics for online course d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…They should further offer teachers the opportunity to develop their own course designs, incorporating and experimenting with instructional strategies, which are central to successful online and blended teaching and learning experiences. These include, for instance, engaging students in and promoting interaction during online activities, which were identified as main challenges in our study, confirming what previous studies had already found (Lee et al, 2011;Martin & Bolliger, 2022). Nevertheless, it is worth noting that such elements -interaction and engagement -were also perceived as beneficial elements.…”
Section: The "Double-edged Sword" Of Otlsupporting
confidence: 89%
See 4 more Smart Citations
“…They should further offer teachers the opportunity to develop their own course designs, incorporating and experimenting with instructional strategies, which are central to successful online and blended teaching and learning experiences. These include, for instance, engaging students in and promoting interaction during online activities, which were identified as main challenges in our study, confirming what previous studies had already found (Lee et al, 2011;Martin & Bolliger, 2022). Nevertheless, it is worth noting that such elements -interaction and engagement -were also perceived as beneficial elements.…”
Section: The "Double-edged Sword" Of Otlsupporting
confidence: 89%
“…Another technology-related element refers to digital skills The efficient use of technology depends on these, or lack thereof, and to some extent so does designing effective pedagogies for online teaching and learning (Martin et al, 2019;Martin & Bolliger, 2022). Such as other studies have found (Rivera-Vargas et al, 2021), our study indicates teachers perceived OTL as an opportunity to develop their digital skills.…”
Section: The "Double-edged Sword" Of Otlmentioning
confidence: 61%
See 3 more Smart Citations